Methodological Support for Separate Accounting of the Performance of State Defense contractors (SDc) - N. T. Labyntsev; P. V. Kolesnik (Учёт. Анализ. Аудит)
Currently, the Russian Federation invests heavily in the production of products under the state defense order (hereinafter — SDO). The head executors and executors of the state budget are obliged to ensure separate accounting of the results of financial and economic activities for each state contract. The article is devoted to the development of methodological support for separate accounting of performance at enterprises which are the executors of the state budget. The research methodology is an analysis of existing methodological approaches to separate accounting of financial results of the SDO and the construction of the author’s own methodology on their basis. The article offers recommendations on the organization and methodology of separate accounting of the results of financial and economic activity by the organizations-executors of the SDO. The author’s definition of the term “separate accounting of the results of financial and economic activities in SDO” is given. The form of the register of accounting for grouping of the actual costs for execution of the SDO is developed. The developed recommendations for management job order costing accounting, clearance accounting, classification of costs by types, and the formation of registers of analytical accounting will allow the organizations-executors of the SDO to keep separate records in accordance with the regulatory requirements and to obtain information on the financial results of each contract at any given time.